Economic Crisis, Tourism Development, and Labor: The Case of Workers in the Community of Los Pargos, Guanacaste - Morales Zúñiga, Luis Carlos (2011)
The article is an extract from a larger investigation on workers who have beendisplaced from traditional economic activities in the community called Los Pargos, in Guanacaste, Costa Rica, and are inserted into the tourism job market. On these workers we analyzed the perception they had in relation to the global economic crisis which most difficult moment was evident in 2009, at which time we were doing the field research. It emphasizes the historical and social moment, as it expressed the fragility of the tourism-dependent economy, which has a direct and detrimental effect on workers who occupy the lowest part of the employment structure of the tourism sector.